Randomised prospective comparative analysis of functional outcome of osteosynthesis of intra-articular distal humerus fracture using triceps reflecting and transolecrenon approach - Jagadeesh, Nuthan; Sanil, Nibin; M. S., Vishwanath (International Journal of Research in Orthopaedics, 2020)
Background: Intra articular fractures of distal humerus is one of the demanding injuries to manage due to its complex anatomy. Open reduction internal fixation is able to achieve painless, stable and mobile joint. This study is aimed at comparing functional outcome of patients treated with triceps reflecting and olecranon osteotomy approach. Methods: A hospital based randomized comparative study of 40 patients who diagnosed with distal humerus intraarticular fracture admitted in our hospital from April 2017 to March 2019. Triceps reflecting approach (group A) was used in 20 patients and olecranon osteotomy approach (group B) in 20 patients. Elbow range of movements and Mayo elbow performance score (MEPS) was used to compare outcome. Results: The mean elbow range of motion is 95.8±13.5 degree at 1 year follow up in group A and 94.5±9.3 degree in 1 year follow up at 1 year follow up in group B. The mean MEP score at end of 1 year in group A was 93.8±2.9 and in group B was 91.5±3.2 shows excellent results but there was no statistically significant difference between MEP scores of two groups. We observed 6 patients developed extension lag less than 10 degree in group A which was clinically insignificant to patients and 7 patients developed hardware prominence in group B. Conclusions: Triceps reflecting Bryan Morrey approach is equally effective as olecranon osteotomy approach in treatment of distal humerus intra articular fracture with less complication and operative time.